Assessment of Internet Banking Services Continued Use: Role of Socio-Cognitive and Relational View - Mira Kartiwi; Ali Rfieda (Universitas Ahmad Dahlan, 2018)
Recently, continued use of information systems in general and particularly the context of internet banking has drawn increasing attention both in academic and trade literatures. However, different perspectives that determine the continued use of internet banking has been addressed. Given the long-term goal of any business entity is to increase its productivity, expand its customer base and maximize revenues, it is crucial for banks offering internet banking services to focus on encouraging their customers to continually use internet banking. While emerging attention had been given on the assessment of continued use of internet banking services from single view, little of attention were given from researchers to combine different views in a single comprehensive model. Yet, it is believe that combining different views would provide a better understanding to the issues surrounding the continued use. Drawing on the literature, this study developed a model to determine factors that influence the continued use of internet banking by combining factors from the socio-cognitive view and the relational view. Using a survey questionnaire, 450 questionnaires were distributed to users of internet banking in Libya. A number of interesting findings emerged, among others, is the lack of association between trust and perception to continue using the internet banking services in Libya.